Root coverage using acellular dermal matrix and comparing a coronally positioned tunnel to a coronally positioned flap approach - Papageorgakopoulos, Georgios; Greenwell, Henry; Hill, Margaret; Vidal, Ricardo; Scheetz, James P (Journal of periodontology (1970), 2008)
The primary aim of this randomized, controlled, masked clinical trial was to compare the percentage of root coverage obtained with a coronally positioned flap plus acellular dermal matrix (ADM) allograft to that of a tunnel technique plus ADM 4 months post-surgically. Twenty-four subjects with one site with > or =3 mm Miller Class I or II recession were treated and followed for 4 months. Twelve patients received a coronally positioned flap plus ADM and were considered the positive control group (CPF). The test group consisted of 12 subjects treated with a coronally positioned tunnel technique plus ADM (TUN). Subjects were randomly selected by a coin toss to receive the test or control treatment. The mean facial recession defect at the initial examination for the TUN group was 3.1 +/- 0.3 mm; this was reduced to 0.7 +/- 0.9 mm at the 4-month examination for a gain of 2.4 +/- 1.0 mm or 78% defect coverage (P <0.05). The mean facial recession defect at the initial examination for the CPF group was 3.4 +/- 0.8 mm; it was reduced to 0.2 +/- 0.3 mm at the 4-month examination for a gain of 3.2 +/- 0.9 mm or 95% defect coverage (P <0.05). There was no statistically significant difference between groups (P >0.05). The coronally positioned flap plus ADM produced a defect coverage of 95%, whereas the tunnel technique plus ADM produced only 78% coverage. This difference was considered clinically significant but was not statistically significant.